Analisis Perubahan Makna Meluas dalam Cerpen Badai yang Reda Karya Fauzia A. - Katharina Woli Namang; Tiara Oktaviani (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study is motivated by language where language always produces new words and new meanings that aim to meet the needs in communicating. The problem discussed is how many changes in widespread meaning are found in the short story Badai Yang Susua by Fauzia A. and how does the change in meaning expand when compared to denotative meaning or actual meaning. Based on the results of the discussion, 11 (eleven) forms of widespread meaning change were found in the short story Badai Yang Susua by Fauzia A.